Peculiaridades canónicas sobre la responsabilidad penal de las personas jurídicas La posible aplicación de la figura del «compliance officer» - Viana, Antonio (2022)
The first section of the text deals with the canonical legal framework of governance and organization to be assessed in court before the possible criminal liability of ecclesiastical realities - in particular, dioceses and parishes. The second section explores the advantages and disadvantages of applying the figure of the compliance officer to ecclesiastical entities.
Keywords: Oficios eclesiásticos; Responsabilidad penal de los entes eclesiásticos; compliance officer; Persona iuridica